Meningkatkan Kemampuan Berpikir Kritis Melalui PBL pada Materi Sepuluh Perintah Allah Fase B Kelas 4 SD N 3 Sijambur - Timawar Nadeak (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to enhance students' critical thinking skills through the implementation of Problem-Based Learning (PBL) on the Ten Commandments material for 4th-grade students in phase B at SD N 3 Sijambur. PBL encourages students to explore and solve contextual problems related to the understanding and application of the Ten Commandments in daily life. This method promotes critical thinking, collaborative learning, and the development of analytical and reflective skills. The results of the study show a significant improvement in students' critical thinking abilities, particularly in identifying problems, formulating relevant solutions, and evaluating information logically. Thus, the application of PBL in this material contributes positively to the development of students' critical thinking skills